Incidence of sexually transmitted infections before and after preexposure prophylaxis for HIV. (20th February 2018) - Nguyen, Vinh-Kim; Greenwald, Zoë R.; Trottier, Helen; Cadieux, Martha; Goyette, Alexandre; Beauchemin, Mariève; Charest, Louise; Longpré, Danièle; Lavoie, Stéphane; Tossa, Hermione Gbego; Thomas, Réjean
Abstract : Objective: Use of preexposure prophylaxis (PrEP) for HIV raises concerns about sexually transmitted infection (STI) incidence because of decreased condom use among MSM. This study examines whether PrEP is associated with STIs in the 12 months following PrEP prescription relative to the 12 months prior to PrEP and if STI rates are higher among PrEP users relative to individuals receiving postexposure prophylaxis (PEP). Design: Retrospective cohort study including PrEP users with more than 12 months of follow-up before PrEP prescription and individuals receiving PEP from 2010 to 2015 at Clinique l'Actuel (Montréal, Canada). Methods: Incidence of chlamydia, gonorrhoea, syphilis and hepatitis C virus over 12 months was compared before and after PrEP; and for PrEP versus PEP users using Poisson models to generate incidence rate ratios (IRRs) with 95% confidence intervals (CIs) and adjusted IRRs (aIRRs) controlling for frequency of STI-screening visits. Models comparing PrEP and PEP users were further adjusted for age and education. Results: One hundred and nine PrEP and 86 PEP users were included. Increased rates of STIs were observed in the 12 months after PrEP relative to the 12 months prior (IRR: 1.72, CI: 1.22–2.41; aIRR: 1.39, CI 0.98–1.96). PrEP users were also at higher STI risk relative to PEP users (IRR: 2.18, CI: 1.46–3.24; aIRR: 1.76, CI: 1.14–2.71). Conclusion: Increased rates of STIs among individuals after initiation of PrEP may suggest greater risk behaviours during the first year on PrEP. Further studies are needed to measure long-term trends in STI acquisition following PrEP initiation.